Application of the Student Teams Achievement Division (STAD) Type Cooperative Learning Model to Improve Science Learning Outcomes of Class VIII Students at UPTD SMP Negeri 1 Alasa for the 2022/2023 Academic Year - Erfin Noderius Hulu; Natalia K. Lase (CV. Rayyan Dwi Bharata, 2023)
Based on the results of initial observations at SMP Negeri 1 Alasa, several problems were found, namely: 1) Students were not actively involved in learning activities, and 2) Student learning outcomes in science subjects were still low. Research objectives: (1) Describe the implementation of the learning process through the application of cooperative learning models of the Student Teams Achievement Division type. (2) Describe student learning outcomes through the application of cooperative learning models of the Student Teams Achievement Division type. The research location is at SMP Negeri 1 Alasa. The research subjects were 30 students in class VIII-4, consisting of 16 boys and 14 girls. The research method used was classroom action research which consisted of four stages: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. Research instruments: (1) observation sheet, (2) learning quality questionnaire, (3) student learning achievement test, (4) interview guide sheets, and (5) photo documentation. The results of the study: (1) Implementation of the learning process through the application of the Student Teams Achievement Division cooperative learning model in science subjects in Cycle I, namely 45.14% with poor criteria and Cycle II, namely 81.25% with good criteria. (2) Student learning outcomes through the application of the cooperative learning model type Student Teams Achievement Division in science subjects in Cycle I, namely 68.33 with sufficient criteria and Cycle II, namely 80.67 with good criteria.